Long-Term Local Injection of RAGE-Aptamer Suppresses the Growth of Malignant Melanoma in Nude Mice. (4th September 2019) - Nakamura, Nobutaka; Matsui, Takanori; Nishino, Yuri; Sotokawauchi, Ami; Higashimoto, Yuichiro; Yamagishi, Sho-ichi
Abstract : Accumulating evidence has suggested the pathological role of advanced glycation end products (AGEs) and their receptor RAGE axis in aging-associated disorders, including cancers. In this study, we examined the effects of local injection of RAGE-aptamer adjacent to the tumor on G361 melanoma growth in nude mice. We further investigated the effects of RAGE-aptamer on oxidative stress generation, RAGE, vascular endothelial growth factor (VEGF), and monocyte chemoattractant protein-1 (MCP-1) gene expression in N ε -(carboxymethyl)lysine (CML)-exposed G361 melanoma cells in vitro . Local injection of RAGE-aptamer adjacent to the tumor dramatically decreased the growth of G361 melanoma in nude mice, which was associated with reduced expression of CML, RAGE, nitrotyrosine, VEGF, CD31, and von Willebrand factor, markers of endothelial cells in G361 tumors. Furthermore, RAGE-aptamer inhibited the binding of CML to V-domain of RAGE and blocked the CML-induced increases in oxidative stress generation, RAGE, VEGF, and MCP-1 mRNA levels in G361 melanoma cells. Our present findings suggest that long-term local injection of RAGE-aptamer adjacent to the tumor could inhibit melanoma growth in nude mice partly by suppressing tumor angiogenesis via blockade of the CML-RAGE interaction. Local injection of RAGE-aptamer may be a feasible therapeutic tool for the treatment of malignant melanoma.